Implications of storage state behaviour of village tanks in adaptation to climate change, Sri Lanka - K. T. N. Perera (IWA Publishing, 2021)
Following Decision 1/CP.21 of the Conference of the Parties, Sri Lanka has identified Nationally Determined Contributions for adaptation to climate change. Restoration and rehabilitation of all abandoned tanks is one such contribution in the irrigation sector. The country has around 13,600 working village tanks of ancient origin. These restored tanks provide irrigation and other water needs at different degrees while a large number of tanks remain abandoned. However, regional storage behaviour of the restored tanks is not adequately understood due to the non-existence of a methodology for storage data collection and assessment. The study presents a statistical approach to assess regional storage behaviour of the tanks with data collected using five storage states method. The storage data of 573 working village tanks in southern Sri Lanka covering three years were analyzed, and revealed a high temporal variation of storage behaviour and low resilience to recover from either dryness or failure for providing irrigation water issues. However, higher time-reliability of water-existence below sluice sill level indicates their potential for providing social and environmental needs. Such assessments facilitate identifying real-time management measures and reviewing policy on restoration of similar reservoirs as an adaptation option for climate change in any region. HIGHLIGHTS Use of five state assessment methods to monitor the storage behaviour of small scale reservoirs where storage measurements are not available.; Use of statistical approach to analyse storage behavoiur on a regional basis.; Analysis of storage behaviour using storage state and storage state transitions.; Comparison of seasonal storage behavior of reservoirs using state transition probabilities.; Assessment of resilience and reliability of reservoirs using storage state behaviour.;